The Impact of Implementing a Specific Time Work Agreement (PKWT) on the Performance of Contract Employees at PT Yachiyo Trimitra Indonesia - Fauzobihi, Fauzobihi; Lamet, Bonaventura; Syaifullah, M. (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
In Indonesia, matters related to how work is carried out always begin with an agreement between the employer and the recipient of the work through a written or verbal work agreement. An employment agreement is made to determine the boundaries between what are the rights and obligations of the employee and what are the rights and obligations of the employer (employer). Meanwhile, if in carrying out work that has been mutually agreed upon in a written agreement, one of the parties violates or behaves outside of what has been agreed upon and harms one of the parties or violates the provisions of the law, then the work agreement can be canceled and the rights and obligations of the parties must be resolved through a dispute resolution mechanism by referring to the applicable laws. Of course, the work agreement text that has been mutually agreed between the employer and the recipient of the work is also an important document for resolving disputes between the parties. Since the promulgation of Law Number 11 of 2020 concerning Job Creation, especially the regulations contained in Government Regulation Number 35 of 2021 concerning "Specified Time Work Agreements, Outsourcing, Working Time and Rest Time, and Termination of Employment Relations," there have been many changes in implementation. specific time work agreement (PKWT). This will of course affect the performance of workers whose work status is as PKWT workers. The impact that arises for PKWT workers on their work performance can be positive or negative. This change in the implementation of the PKWT is certainly a very important thing, because if it is not controlled properly it will result in an automatic change in the status of workers from having the status of a fixed-term work agreement to an indefinite-term work agreement, as well as the rights and obligations obtained by workers. will change.